THE LINGUISTICS OF CODE-SWITCHING: NAVIGATING MULTIPLE DIALECTS AND LANGUAGES IN CONVERSATIONS (Web of Teachers: Inderscience Research, 2025)
This article explores the linguistics of code-switching, a phenomenon where speakers alternate between multiple languages or dialects within a single conversation. Code-switching is a complex and dynamic linguistic practice that reflects the cultural, social, and contextual influences shaping language use. It occurs across various domains, including multilingual communities, social media, and professional environments, often as a strategy to express identity, convey specific meanings, or navigate complex social relationships. By examining the cognitive, sociolinguistic, and pragmatic aspects of code-switching, the article highlights its role in communication, demonstrating how speakers harness multiple languages or dialects to meet communicative goals. Additionally, the study delves into the implications of code-switching for language development, language contact, and the preservation of cultural identities in multilingual contexts.